Exceptionally early tympanostomy tube placement in pediatric patients with cleft lip and palate. (June 2021) - Koempel, Jeffrey; Osterbauer, Beth; Badash, Ido; Goel, Pedram; Fahradyan, Artur; Zhang, Zhipeng; Hammoudeh, Jeffrey
Abstract: Objective: At our institution, cleft lip repair is performed at or before 8 weeks of age, and tympanostomy tubes (TT) have been inserted concurrently in some of these patients. Our objective was to determine the feasibility and present the preliminary results of TT placement at this early age. Methods: A retrospective review was conducted of 22 patients born with cleft lip and/or palate who had TT placement in the first 8 weeks of life. Data collected included complications and audiologic function post TT placement. Results: Subjects had a mean age of 3.9 weeks at the time of TT placement and cleft lip repair. Thirteen patients (59%) reported otorrhea during the follow-up period. Eighteen of 21 (86%) patients who underwent auditory evaluation had normal audiological function following TT placement. One patient had sensorineural hearing loss and 2 patients had mild conductive hearing loss due to bilateral extruded TT and OME at 15.9 and 39.2 months after surgery. Conclusion: Exceptionally early TT is feasible. Placing TT at or before 8 weeks of age did not result in any major complications but demonstrated a high incidence of otorrhea. A randomized, prospective study with a larger sample size is necessary to determine the benefits of TT placement at this age. Highlights: This is the first report of tympanostomy tube placement in cleft patients before 8 weeks of life. Tympanostomy tube (TT) insertion at less than 8 weeks of age is feasible. Placing TT before 8 weeks of age results in no major complications and a comparable rate of otorrhea.